Microstructure and mechanical properties of metallic components by selective laser melting (SLM) - Teo, Larry Fu Quan (2015)
Many researches have been conducted in the area of 3D printing and selective laser melting of various metal alloys to attempt to achieve full density printed metal components. Various parameters such as laser power can be varied to optimise the density of the metal components, however full density metal model using selective laser melting alone is yet to be achieved. A decrease in density of the metal would mean an increase in porosity and therefore a decrease in young’s modulus of the material. This paper will look at how does the change in young’s modulus affect the load-bearing capability of the material using finite element modelling or analysis. Various structural geometries will also be investigated to find out which model has the best effective young’s modulus. It can be concluded that a decrease in young’s modulus has an adverse effect on the material load-bearing capability and that a vertical bar model has the best specific effective young’s modulus.